PENGEMBANGAN SOAL BIOLOGI BERBASIS HIGHER ORDER THINKING SKILL (HOTS) DENGAN APLIKASI QUIZIZZ MATERI SISTEM PENCERNAAN MANUSIA - Umi Rahmah; Muhfahroyin Muhfahroyin; Triana Asih (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
This research aimed to produce a product based on Higher Order Thinking Skill (HOTS) biology questions with the Quizizz application for the human digestive system. This type of research was development research that used the 4D Thiagarajan method. The stages of this research method include define, design Develop, and Disseminate. The development stage contains validation and revision. Validation carried out included validation of design experts (by 2 lecturers), and an expert validation of HOTS questions (by 1 lecturer and 1 teacher). Validation was carried out to see the feasibility of the product before being tested on students in small group trials. The results of the study stated that the development of Higher Order Thinking Skill (HOTS)-based biology questions with the Quizizz application for the human digestive system material was declared eligible to be used with a very good category based on the design display was 86%, the substantial component of the HOTS question content 91.35% and student response questionnaires 90.5%.